Make it safe : a guide to food safety. (CSIRO Publishing, 2010)
Publisher's description: All people involved with preparation of food for the commercial or retail market need a sound understanding of the food safety risks associated with their specific products and, importantly, how to control these risks. Failure to control food safety hazards can have devastating consequences for not only the consumer, but also the food manufacturer. Make It Safe provides practical guidance on how to control food safety hazards, with a specific focus on controls suitable for small-scale businesses to implement. Small businesses make up around two-thirds of businesses in Australia's food and beverage manufacturing industry. This book is aimed at those small-scale businesses already in or considering entering food manufacture. Those already operating a small business will develop a better understanding of key food safety systems, while those who are in the 'start-up' phase will gain knowledge essential to provide their business with a solid food safety foundation while also learning about Australian food regulations relevant to food safety. The content will also be useful for students studying food technology or hospitality who wish to seek employment in the manufacturing industry or are planning on establishing their own manufacturing operation. Illustrated in full colour throughout, Make It Safe outlines the major food safety hazards - microbial, chemical and physical - which must be controlled when manufacturing all types of food products. The control of microbial hazards is given special emphasis as this is the greatest challenge to food manufacturers. Topics covered include: premises, equipment, staff, product recipes, raw ingredients, preparation, processing, packaging, shelf-life, labelling and food recalls. Key messages are highlighted at the end of each chapter.